TATA KELOLA BADAN USAHA MILIK DESA (BUMDes) DALAM MENINGKATKAN PENDAPATAN ASLI DESA (PADes) - Moh. Asadi; Ansari Ansari (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2023)
This capacity building aims to improve the economy and welfare of villagers through the development of economic enterprises. In addition, BUMDes also have an effect on increasing village original income (PADes) which is able to enable villages to carry out development and for the development of community welfare. This research method uses a qualitative approach perspective and the nature of descriptive research, while the data collection technique uses observation, interviews, and documentation. While data analysis techniques in qualitative research using interactive analysis models are an analysis process carried out in conjunction with the data collection process. The results showed that; 1). Transparency and available information include the vision and mission of BUMDes Desa Bangunsari, work programs and management structure. The information can be accessed by the public by asking questions directly. Information that is not yet available is information about financial data. 2). Accountability for the duties and responsibilities of each rank, but not all duties and responsibilities are detailed in writing. 3). Fairness in managing Bungunsari BUMDes involves related parties even to capital owners in this case villages in the decision-making process. 4). The responsibility of Bangunsari BUMDes is carried out by complying with applicable regulations such as Bangunsari Village Regulation Number 04 of 2016 concerning the establishment of Village-Owned Enterprises (BUMDes), and always paying attention to the interests of the community and the environment.